THE OUTCOME OF INTRAVITREAL BROLUCIZUMAB FOR NEOVASCULAR AGE-RELATED MACULAR DEGENERATION TREATMENT: Poster Presentation - Case Report - Resident - Graziani, Gabriella; Ihsan, Grimaldi; Widyanatha, Made Indra; Virgana, Rova; Kartasasmita, Arief S.; Iskandar, Erwin (Majalah Oftalmologi Indonesia, 2023)
Introduction : Age-related macular degeneration (AMD) is a disease that results in irreversible severe loss of central vision in people over 50 years old. Hence, anti-VEGF therapy has become a standard treatment for neovascular AMD. Brolucizumab is a single-chain antibody fragment that inhibits VEGF-A binding to VEGF receptors. It has a higher molar concentration that allows a greater reduction in the central subfield thickness (CST) Case Illustration : A 59-year-old male with a chief complaint of gradually blurred vision in the left eye for 2 years. BCVA of the left eye was 0.3, OCT showed a hyperreflective band in the sub-neurosensory space with subretinal fluid in the left eye (Figure 1), and OCT-A revealed choroidal neovascularization (Figure 2). The patient was diagnosed with AMD AREDS IV in the left eye. He had undergone three monthly injections of brolucizumab. BCVA of the left eye after injection improved to 1.0 and OCT imaging showed no subretinal fluid, no intraretinal fluid, and no pigment epithelial detachment. Discussion : Brolucizumab has a greater reduction in CST because of its high molecular concentration. Results of HAWK and HARRIER concluded that brolucizumab was non-inferior towards aflibercept in BCVA change at week 48. According to the HAWK trial, a greater reduction of CST was seen in week 16 among eyes treated with brolucizumab. Brolucizumab was also well tolerated and adverse event rates were similar to aflibercept. Conclusion : Brolucizumab could be an alternative treatment option considering its efficacy in improving visual acuity and reducing CST.